TRANSACTION COSTS OF TRADING IN ORGANIZED STOCK MARKETS: STRUCTURE AND IMPLICATIONS FOR MARKET EFFICIENCY - LIUBKINA, Olena; IHNATIUK, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article substantiates the origin of transaction costs of stock trading from the point of view of the microstructure of the stock market. The article is devoted to the problem of improving the efficiency of decision-making in the field of portfolio investment, in particular in terms of reducing the cost of conducting operations. The object is the microstructure of the stock market, which allows to study in detail the process of making transactions with securities. The origin of transaction costs of stock trading was determined from the point of view of the microstructure of the market: as an appropriate fee for urgency and certainty in the purchase and sale process; as the premium for participation in market trading and conducting the exchange to stimulate potential counterparties; as the result of potential discrepancy in terms of information that the participants of exchange operations have. The classification of transaction costs is systematized according to various criteria: clarity of identification and assessment (explicit – commissions of intermediaries and the stock exchange, taxes, etc.and implicit – costs of spread, timeliness, market impact, missed opportunities); according to the reason for the various transaction costs (taxes, commissions, transaction execution costs and costs of missed opportunities). It is established that implicit costs add a significant level of uncertainty to the investment decision-making process, and therefore their evaluation and control is a priority issue for the investment entity. The main approaches to quantification of implicit transaction costs – missed opportunity costs, spread costs, and market impact costs-are summarized. Prospects for improving the tools for estimating transaction costs of operations in organized stock markets are determined.
Keywords: transaction costs; stock exchange; investment solutions; portfolio investment; developed stock markets; stock market pricing